2018
DOI: 10.23736/s0375-9393.18.12658-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consent to organ donation after brain death certification: a survey of 29 Intensive Care Units

Abstract: Older age of BDCPs and a prolonged ICU LOS resulted in FR. ICU team specific education emerged as the only modifiable protective factor for oppositions, thus continuous and in-depth training programs for physicians and nurses could be of importance in preventing FR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…The main reasons for lack of organ donation include the lack of detection and reporting of cases of brain death and that family members of the potential donor do not agree to donate the organs [ 24 – 27 ]. One of the reasons why family members do not donate organs is that they do not understand brain death [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for lack of organ donation include the lack of detection and reporting of cases of brain death and that family members of the potential donor do not agree to donate the organs [ 24 – 27 ]. One of the reasons why family members do not donate organs is that they do not understand brain death [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 minutes) at the start of these training rotations or be included as part of the junior doctor induction pack to improve the knowledge of corneal and tissue donation. In fact, Piemonte et al 31 found that training for physicians and nurses was the only modifiable factor to improve organ donation in intensive care units. Interestingly, previous discussion with family on corneal donation was not associated with a knowledge of corneal donation.…”
Section: Discussionmentioning
confidence: 99%
“…A maneira como o indivíduo se relaciona com a imagem corporal, pode facilitar ou dificultar a doação. [36][37] Essa teoria pode justificar o fato de menos doações do sexo feminino, uma vez que a mulher, culturalmente é a referência do cuidado e vínculo afetivo.…”
unclassified
“…Avaliando a correlação entre a causa da morte e o resultado das entrevistas, percebeu-se uma maior aceitação da doação de pacientes vítimas de TCE, quando comparados com os pacientes vítimas de AVE, corroborando com outros estudos. 3,37 A doação em casos de morte trágica, com a perda repentina do ente querido, é vista como uma continuação da vida, sendo um conforto para os familiares. Pode-se dizer que a escolha pela doação os ajuda a lidar melhor com a perda e ter um sentimento de tranquilidade no futuro, com a superação do luto.…”
unclassified